Participatory assessment of farmer-led adaptation strategies in livestock rearing to climate change in eastern Uttar Pradesh - Yadav, Preeti; Maiti, Sanjit; Jha, S K; Meena, H R; Bhakat, Mukesh; Dixit, A K (Indian Journal of Dairy Science, 2022)
Climate change is global phenomenon, but, its effect and impact are local as well as region specific. Seasonal variations in rainfall and temperature have influenced the agro-climatic conditions as well as populations of pests, weeds, and diseases leading to a loss in livestock productivity. The present study was conducted in three districts of Eastern Uttar Pradesh; namely, Azamgarh, Varanasi & Ghazipur. 180 respondents were interviewed, of which 143 respondents were following at least one adaptation strategy for livestock. 15 adaptation strategies were documented using Climate Change Adaptation Index (CCAI). Quantification of Indigenous Knowledge (QuIK) method given by Di Villers (1996) was adopted to assess the effectiveness of adaptation strategies with the help of 36 key informants (12 from each district).Â  The incidence of heavy rainfall has increased in the region, so "proper sanitation and healthy practices" and "vaccination" were considered efficient adaptation strategies. In summer, to alleviate heat stress in livestock strategies like â€œproviding extra drinking water and extra bath/shower to livestockâ€ were effective. In the winter season, to protect cattle and buffaloes from cold waves, the â€œuse of jute cloth to cover the body of animalsâ€ was the most effective one.